2017
DOI: 10.1128/jb.00840-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sporangium Formation by BldD in the Rare Actinomycete Actinoplanes missouriensis

Abstract: The rare actinomycete Actinoplanes missouriensis forms sporangia, including hundreds of flagellated spores that start swimming as zoospores after their release. Under conditions suitable for vegetative growth, zoospores stop swimming and germinate. A comparative proteome analysis between zoospores and germinating cells identified 15 proteins that were produced in larger amounts in germinating cells. They include an orthologue of BldD (herein named AmBldD [BldD of A. missouriensis]), which is a transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 31 publications
(24 reference statements)
1
44
0
Order By: Relevance
“…The amplified DNA fragments were analyzed by sequencing to confirm the absence of undesired mutation. Modified pK19mobsacB, the kanamycin resistance gene of which was replaced with the apramycin resistance gene aac(3)IV , was used as a vector for conjugation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplified DNA fragments were analyzed by sequencing to confirm the absence of undesired mutation. Modified pK19mobsacB, the kanamycin resistance gene of which was replaced with the apramycin resistance gene aac(3)IV , was used as a vector for conjugation.…”
Section: Methodsmentioning
confidence: 99%
“…Actinoplanes missouriensis 431 is a rare actinomycete isolated from barnyard soil near Hamilton, Missouri, USA . It shows interesting morphological features and forms sporangia containing motile sporangiospores . We have shown that this strain produces several secondary metabolites, including alkyl‐ O ‐dihydrogeranyl‐methoxyhydroquinones and 3‐hydroxy‐6‐dimethylallylindolin‐2‐one .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other filamentous actinomycetes are usually only a focus for research if they produce an antibiotic or other natural product of potential medical relevance, and their developmental biology is not analyzed. It is for this reason in particular that the work reported by Mouri et al (2) on reproduction in Actinoplanes is so refreshing.…”
mentioning
confidence: 96%
“…Mouri et al (2) noted that the RXD-X 8 -RXXD c-di-GMP-binding signature observed in the Streptomyces BldD-c-di-GMP crystal structure is conserved in Actinoplanes. As a consequence, they used electrophoretic mobility shift assays (EMSAs) to see if c-di-GMP might also control the activity of Actinoplanes BldD and found that it greatly enhanced the binding of Actinoplanes BldD to its target DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation